Saving CeeCee Honeycutt : a novel - Hoffman, Beth (Viking, 2010)
"Steel Magnolias" meets "The Help" in this Southern debut novel sparkling with humor, heart, and feminine wisdom. Laugh-out-loud funny, Hoffman's charming work offers the story of a young girl who loses one mother and finds many others.